Participatory Learning Method: Effectiveness in Improving Student Learning Outcomes - Saroinsong, Djony Max; Dengah, Jenny Ieke; Rondonuwu, Anneke Tienneke (Edumaspul: Jurnal Pendidikan, 2024)
The appropriate learning methods are needed to allow students to learn actively, dare to participate, and interact with each other in learning. This study aims to determine the effectiveness of the participatory learning method in improving student learning outcomes in educational sociology and anthropology courses. This research is a type of quantitative research with pre-experimental research methods and uses the one-group pretest-posttest design as the research design. The subjects in this study were undergraduate students from the nonformal education study program who contracted educational sociology and anthropology courses in the even semester of the 2021/2022 academic year at the Universitas Negeri Manado, with a research sample consisting of 15 students. Data collection techniques using test techniques. The research instrument used was a test of learning outcomes in the form of a pretest and a posttest in the form of a description. The results showed that the average posttest (3.37) was higher than the pretest (1.51). In addition, the average N-gain (g) acquisition score calculation is 0.75, which is included in the high category; thus, applying the participatory learning method effectively improves student learning outcomes in educational sociology and anthropology courses.